Analysis of Expressive Illocutionary Acts in Disney Princess Movie “Moana” - Mohamad Syafri; Nanik Shobikah; Zulfikar Zulfikar (Phonologie : Journal of Language and Literature, 2025)
Abstract. Movies are a reflection of real-life phenomena, including the language phenomenon. Therefore, using the movie from Disney “Moana”, this research analyzes expressive illocutionary acts. As part of the broader speech act theory, expressive acts convey the speaker's psychological state, such as apologizing, thanking, congratulating, wishing, greeting, and expressing attitudes. This study is a descriptive qualitative study through content analysis, using Moana’s movie script as the primary data source. Data were collected through viewing, note-taking, classification, and analysis. Dell Hymes’ SPEAKING model and lexical analysis via AntConc were the primary data analysis methods. The findings reveal that four types of illocutionary acts appear in the film—expressive, commissive, directive, and representative—while declarative acts are absent. Among 559 illocutionary utterances identified, 34% (190) were expressive. "Attitude" is the most frequent (65%) expressive act, and "wishing" is the least (2%). Expressive acts in all types, except wishing, appeared in both direct and indirect forms, often reflecting complex social roles and intentions. Lexical analysis showed that expressive utterances predominantly used common and grammatically relevant vocabulary, suggesting the film's potential as a practical teaching resource, especially for children. Overall, this study not only deepens the understanding of expressive illocutionary acts in animated films but also highlights their relevance in language education contexts.Keyword: Speech Acts, Expressive Illocutionary Acts, Movies, Word Types